2011
DOI: 10.1103/physrevlett.106.172002
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Dijet Azimuthal Decorrelations inppCollisions ats=7TeV

Abstract: Azimuthal decorrelations between the two central jets with the largest transverse momenta are sensitive to the dynamics of events with multiple jets. We present a measurement of the normalized differential cross section based on the full data set (∫Ldt=36  pb(-1)) acquired by the ATLAS detector during the 2010 sqrt(s)=7  TeV proton-proton run of the LHC. The measured distributions include jets with transverse momenta up to 1.3 TeV, probing perturbative QCD in a high-energy regime.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 32 publications
1
44
0
Order By: Relevance
“…Performance studies [50] have shown that there is excellent agreement between the measured positions of clusters and tracks in data, indicating no systematic misalignment between the calorimeter and inner detector. The Monte Carlo modeling of the position of clusters with respect to tracks is also good, indicating that the detector simulation models the calorimeter position resolution adequately; however, there remains a small discrepancy between data and Monte Carlo in the mean and RMS of the track-cluster separation.…”
Section: B Uncertainties On the Detector Materials Description And CLmentioning
confidence: 81%
“…Performance studies [50] have shown that there is excellent agreement between the measured positions of clusters and tracks in data, indicating no systematic misalignment between the calorimeter and inner detector. The Monte Carlo modeling of the position of clusters with respect to tracks is also good, indicating that the detector simulation models the calorimeter position resolution adequately; however, there remains a small discrepancy between data and Monte Carlo in the mean and RMS of the track-cluster separation.…”
Section: B Uncertainties On the Detector Materials Description And CLmentioning
confidence: 81%
“…Track-jets have a different set of systematic uncertainties and allow a reliable determination of the relative systematic uncertainties associated with the calorimeter-based measurement. Performance studies [90] have shown that there is excellent agreement between the measured positions of clusters and tracks in data, indicating no systematic misalignment between the calorimeter and the inner detector. The use of track-jets reduces or eliminates the impact of additional pp collisions by requiring the jet inputs (tracks) to come from the hard-scattering vertex.…”
Section: Jet Mass Scale Validation In Inclusive Jet Events Using Tracmentioning
confidence: 82%
“…1 are dominated by gluon radiation, which is decorrelated from the main event axis as predicted by QCD and measured in Refs. [65,66].…”
Section: Figmentioning
confidence: 99%
“…This is motivated by the track-to-cluster matching studies done in Ref. [65]. This impacts the TEEC measurement at the level of 0.5%.…”
Section: Systematic Uncertaintiesmentioning
confidence: 99%